Material perspectives on religion, conflict, and violence: things of conflict - Liere, Lucien van; Meinema, Erik (Method & theory in the study of religion, 2022)
How do objects become contested in settings characterized by (violent) conflict? Why are some things contested by religious actors? How do religious actors mobilize things in conflict situations and how are conflict and violence experienced by religious groups? This volume explores relations between materiality, religion, and violence by drawing upon two fields of scholarship that have rarely engaged with one another: research on religion and (violent) conflict and the material turn within religious studies. This way, this volume sets the stage for the development of new conceptual and methodological directions in the study of religion-related violent conflict that takes materiality seriously.